1995
DOI: 10.1002/pca.2800060202
|View full text |Cite
|
Sign up to set email alerts
|

Compositional analysis of intact alkyl esters in leaf epicuticular wax of swede by capillary gas chromatography and electron‐impact mass spectrometry

Abstract: A method for the separation and identification of complex mixtures of more than 50 different intact esters in epicuticular wax of swede, Brassica napus var. rapifera cv. Doon Major, using combined gas chromatography‐mass spectrometry (GC‐MS) has been developed. The esters were separated at temperatures of up to 350°C by automatic pressure programming (for capillary GC) or by manually increasing helium carrier gas pressure (for GC‐MS) in order to maintain flow at high temperatures. Esters in the range C41‐C50 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 22 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…In comparison, the effects were reversed for temperature ( gl 2 and gl 3) or showed intermediate product distributions for temperature ( gl 1) and light ( gl 1, gl 2 and gl 3). In another study (Shepherd et al ., 1995b, 1997) with the brassicas kale, B. oleracea , and swede, B. napus , glasshouse‐grown plants (lower irradiation, higher temperature) were compared with plants grown outdoors (higher irradiation, lower temperature). Both species responded similarly under the different conditions, and there was also some similarity with the earlier findings of Baker (1974), decarbonylation products being relatively more abundant under higher irradiation/lower temperatures.…”
Section: Effects Of Irradiation and Temperature On Cuticular Wax Cmentioning
confidence: 92%
See 1 more Smart Citation
“…In comparison, the effects were reversed for temperature ( gl 2 and gl 3) or showed intermediate product distributions for temperature ( gl 1) and light ( gl 1, gl 2 and gl 3). In another study (Shepherd et al ., 1995b, 1997) with the brassicas kale, B. oleracea , and swede, B. napus , glasshouse‐grown plants (lower irradiation, higher temperature) were compared with plants grown outdoors (higher irradiation, lower temperature). Both species responded similarly under the different conditions, and there was also some similarity with the earlier findings of Baker (1974), decarbonylation products being relatively more abundant under higher irradiation/lower temperatures.…”
Section: Effects Of Irradiation and Temperature On Cuticular Wax Cmentioning
confidence: 92%
“…An increase in wax thickness is a response of many plants including various Brassica sp. (Baker, 1974; Reed & Tukey, 1982; Shepherd et al ., 1995b), carnation (Reed & Tukey, 1982) and barley (Giese, 1975) to higher irradiation levels (Tables 2, 4). In her study using barley, Giese (1975) found that deposition rates and leaf‐surface wax density in 4‐d‐old plants were 2.5 times greater in the light than in the dark.…”
Section: Effects Of Irradiation and Temperature On Cuticular Wax Cmentioning
confidence: 99%
“…Since such metamers could not be chromatographically resolved and thus quantified by GC-FID, their distributions were determined instead based on abundances of characteristic fragments in the mixed mass spectrum associated with the GC peak of each ester homolog. 23,31,32,33,34,35 Three different patterns of isomer distributions could be discerned depending on overall ester homolog chain length, Figure 5. In young Phyllostachys aurea leaves, the shorter ester homologs (C36-C42) were formed primarily by C20 alcohol and C16-C22 acids, the mid-range esters (C42-C44) included a large portion of isomers formed by C26-C28 alcohols and C16 acid, while the longer esters (C44-C52) contained mainly C22-C30 alcohols and C22 acid.…”
Section: Homolog / Isomer Distributions Within Cuticular Wax Classesmentioning
confidence: 99%
“…Cutin has a variable and dynamic composition, the ratio of C 16 to C 18 fatty acids may be organ-as well as speciesspecific, and changes during ontogeny [31 -33]. The chemical composition of the epicuticular wax on the aerial surface of a plant varies among species, within species, within parts of individual plants, and within different stages of development [34] [35].…”
mentioning
confidence: 99%